2005
DOI: 10.1161/01.cir.0000163562.82134.8e
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Cardiac Aldosterone Synthesis in Angiotensin II Type 1A Receptor–Knockout Mice After Myocardial Infarction

Abstract: Background-The renin-angiotensin-aldosterone system is implicated in the pathogenesis of heart failure. Pharmacological blockade of angiotensin II (Ang II)-dependent signaling is clinically effective in reducing cardiovascular events after myocardial infarction (MI) but still fails to completely prevent remodeling. The molecular basis underlying this Ang II-independent remodeling is unclear. Methods and Results-Acute MI was induced by coronary ligation in wild-type (WT) and angiotensin II type IA receptor-knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 40 publications
1
31
0
1
Order By: Relevance
“…In view of the tissue-specific activation of myocardial aldosterone, Silvestre et al have already reported that MI raises aldosterone synthase (CYP11B2) mRNA by 2.0-fold and the aldosterone level by 3.7-fold in rats (39). More recently, Katada et al have reported that gene expression levels of aldosterone synthase and cardiac aldosterone content are both elevated in MI hearts even in angiotensin II type 1A receptor-knockout mice (40). In various epithelial cells, expression of 11β-HSD2 converts endogenous glucocorticoids to their receptor-inactive 11-keto analogs, thereby conferring aldosterone selectivity on MR (41).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the tissue-specific activation of myocardial aldosterone, Silvestre et al have already reported that MI raises aldosterone synthase (CYP11B2) mRNA by 2.0-fold and the aldosterone level by 3.7-fold in rats (39). More recently, Katada et al have reported that gene expression levels of aldosterone synthase and cardiac aldosterone content are both elevated in MI hearts even in angiotensin II type 1A receptor-knockout mice (40). In various epithelial cells, expression of 11β-HSD2 converts endogenous glucocorticoids to their receptor-inactive 11-keto analogs, thereby conferring aldosterone selectivity on MR (41).…”
Section: Discussionmentioning
confidence: 99%
“…This does not exclude the possibility that local production of aldosterone becomes an important determinant of cardiac aldosterone levels under pathological conditions. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Elevation of BP also might not be necessary for Ald-NaCl-induced cardiac fibrosis, because in the present study, AT1aR-KO treated with Ald-NaCl showed an SBP comparable to that of Wt treated with NaCl alone, which showed much milder cardiac fibrosis. Katada et al recently reported the importance of aldosterone on cardiac remodeling after myocardial infarction in AT1aR-KO (25). In their report, induction of myocardial infarction increased the production of aldosterone in the hearts of AT1aR-KO, and spironolactone prevented the cardiac fibrosis with the reduction of gene expression of collagens and natriuretic peptides (25).…”
Section: Angiotensin II Receptor and Aldosteronementioning
confidence: 97%
“…Katada et al recently reported the importance of aldosterone on cardiac remodeling after myocardial infarction in AT1aR-KO (25). In their report, induction of myocardial infarction increased the production of aldosterone in the hearts of AT1aR-KO, and spironolactone prevented the cardiac fibrosis with the reduction of gene expression of collagens and natriuretic peptides (25).…”
Section: Angiotensin II Receptor and Aldosteronementioning
confidence: 97%